THE ROLE OF DILEMMAS IN LAW - Azevedo, Sara (Pravni zapisi, 2024)
It is widely recognized that the application of legal norms can lead to normative conflicts. Alongside the notion of normative conflict, the concept of legal di- lemma has gained prominence, although its use in legal discourse raises several questions. First, the concept of legal dilemma is a reproduction, mutatis mutandis, of the concept of dilemma developed in moral philosophy. Second, some legal scholars focus exclusively on constitutional dilemmas (i.e., legal dilemmas involving constitutional norms), seemingly assuming that this is a phenomenon limited to the application of constitutional norms. This paper examines how the concept of dilemma is defined in moral philosophy and discusses whether and to what extent the proposals developed in that field can be imported into the legal world. The aim of this paper is to clarify what is usually meant by legal and constitutional dilemmas, and to identify the advantages and inconveniences of using these concepts in legal discourse.